PENDAMPINGAN PASTORAL TERHADAP PECANDU NARKOBA DI YAYASAN REHABILITASI RUMAH DAMAI SEMARANG - Elitri Santi Zebua; Yusup Rogo Yuono; Chlaodhius Budianto; Agung Dian Rengganis; Daryanto (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2022)
This research is about pastoral dependence on drug addicts which was carried out by the Rumah Damai Rehabilitation Foundation in Semarang to help and assist people who help in drugs, with their aim to appreciate and receive and experience love as in the Peace House Rehabilitation Foundation that “My Family is My Home.